2012
DOI: 10.1371/journal.pone.0047693
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Proper Trafficking to the Cell Surface for Membrane Proteins Harboring Cysteine Mutations

Abstract: A common phenotype for many genetic diseases is that the cell is unable to deliver full-length membrane proteins to the cell surface. For some forms of autism, hereditary spherocytosis and color blindness, the culprits are single point mutations to cysteine. We have studied two inheritable cysteine mutants of cyclic nucleotide-gated channels that produce achromatopsia, a common form of severe color blindness. By taking advantage of the reactivity of cysteine’s sulfhydryl group, we modified these mutants with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previously, CNGA3 mutations had been reported in 81 families, including 76 families with total color blindness (or achromatopsia), 13,15,16,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] three families with progressive COD, 13,16 a family with LCA, 17 and a family with oligocone trichromacy 44 according to information from an online database (HGMD Professional [https://portal.biobase-international .com/hgmd/pro/gene.php?gene=CNGA3]). One study 16 also indicated that CNGA3 mutations detected in achromatopsia were also present in patients with CORDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, CNGA3 mutations had been reported in 81 families, including 76 families with total color blindness (or achromatopsia), 13,15,16,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] three families with progressive COD, 13,16 a family with LCA, 17 and a family with oligocone trichromacy 44 according to information from an online database (HGMD Professional [https://portal.biobase-international .com/hgmd/pro/gene.php?gene=CNGA3]). One study 16 also indicated that CNGA3 mutations detected in achromatopsia were also present in patients with CORDs.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, an online database (HGMD Professional) reports 81 CNGA3 mutations, including 69 missense, 13,[15][16][17][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] eight nonsense, 16,27,29 three small insertion, 16,27 and a small deletion. 16 In the present study, 39 CNGA3 variants were detected, including 26 novel and 13 known mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation often starts while MP is translocated into the ER, and a preassembled polymannose oligosaccharide is transferred to the luminal N-aminoacidic residue of the classic motif including asparagine-X-serine/threonine(N-X-S/T) as a consensus sequence. Once in the Golgi, some enzymatic reactions can add sugar moieties or just modify the preexisting glycan tree complexity [121][122][123].…”
Section: Membrane Protein Modificationsmentioning
confidence: 99%
“…Glycerol [312]. MTSHB (Hydroxybenzyl-Methanethiosulfonate), MTSEA (Aminoethyl-Methanethiosulfonate) [123].…”
Section: Cyclic Nucleotide Gated (Cng) Channelmentioning
confidence: 99%
“…8,9 The introduction of such an artificial moiety at the appropriate site allows the acquisition by the target protein of activities and/or structures that are suitable for the desired purpose and that are not necessarily related to its original biological functions. 16 Here, we propose a rather different approach to protein engineering compared with the conventional molecular design. In this context, Lopez-Rodriguez et al have recently reported the replacement of amino acid side chains with synthetic moieties with chemical properties that were similar to those of the original side chain.…”
Section: Introductionmentioning
confidence: 99%